Tinjauan Literatur Sistematis : Faktor yang memengaruhi kesuksesan Portofolio Proyek - Anggi Darmansyah; Budhi Prihartono (Program Studi Teknik Industri, Fakultas Teknologi Industri, Institut Teknologi Bandung, 2026)
In an increasingly complex and dynamic business environment, project portfolios are becoming a means to achieve strategic objectives and a company's competitive advantage. Achieving project portfolio success requires knowledge of the factors that influence that success. Knowledge of these factors is necessary to ensure that project portfolio management takes them into account. However, no research has summarized the factors that influence the success of project portfolios. Therefore, this study aims to conduct a systematic literature review related to the factors that influence the success of project portfolios in companies. This review was conducted using the PRISMA model, which is based on the stages that must be carried out to obtain articles that align with the research objectives. The search for these success factors was conducted using keywords in nine databases for the period 1988–2024. The final search results indicate that there are eight factors that influence the success of project portfolios that need to be considered in project portfolio management in companies. These factors include Stakeholders, Strategic, Ideation, Culture, Governance, Process, Risk, and Resources.